Semiannual Kelvin Waves Propagation along the South Coast of Sumatra-Jawa-Bali and the Lesser Sunda Islands Observed by TOPEX/POSEIDON and ERS-1/2 Satellites - Syamsudin, F. (Journal of Engineering and Technological Sciences, 2004)
The merged TOPEX/POSEIDON (T/P) and ERS-1/2 altimeter data during 10/14/1993 â 2/12/2002 have been used to study Indian Ocean Kelvin waves propagation along the south coast of Jawa, Bali, Lombok, and the Lesser Sunda Islands. The results show that the occurrence of semiannual Indian Ocean Kelvin waves either in April/May or November/December for all the year of 1993-2001 (except in 1994) with the intraseasonal period and phase speed ranging from 35 to 90-day and 1.54 to 2.9 m/s, respectively.